Malocclusion Characteristics as Risk Factors for Temporomandibular Disorders: Lessons Learned from a Meta-Analysis. (19th August 2015) - Cruz, Claudia L.; Lee, Kevin C.; Park, Jae Hyun; Zavras, Athanasios I.
Abstract : The objective of this meta-analysis was to evaluate the association of various malocclusion characteristics with temporomandibular disorders (TMDs). Two reviewers identified articles through database searches of MEDLINE (Ovid) and LILACS and hand searches of major orthodontic journals and selected references. Random-effects models were used to calculate weighted pooled odds ratio (OR) estimates of malocclusion exposures. Six articles qualified for inclusion in the final quantitative analysis. Our study found that static occlusal factors had no significant association with TMD. Of the dynamic occlusal factors assessed, only the absence of canine guidance, laterotrusive interferences, and retruded contact position to maximal intercuspation slide length ≥2 mm demonstrated significant ORs. These results should be viewed with caution, as reporting biases were difficult to assess, and heterogeneity estimates may have been underestimated due to the limited number of studies within each comparison. TMD is a term that encompasses a broad group of dysfunctions, and meta-analyses should only synthesize studies with similar diagnostic criteria. At the present, there is a paucity of studies available that could be properly synthesized to answer the research question posed. Individual studies have too much variability among their methods, and researchers need to clearly define and state their TMD factor definition.